(untitled) (Vietnam Journal of Community Medicine, 2026)
Background: Angry/agitated patients are common in clinical practice and may lead to conflict and workplace violence. Objectives: To synthesize evidence on patient anger, communication strategies, and de-escalation training in nursing. Methods: An evidence-informed methodological narrative review was conducted in PubMed, Scopus, Web of Science, and CINAHL for studies published from January 2010 to 1 March 2026. Results: De-escalation includes active listening, empathy, voice control, non-verbal communication, emotional self-regulation, and problem-solving. Training may improve short-term knowledge, attitudes, and confidence, whereas evidence for reducing actual violence remains inconsistent. Conclusions: Communication skills are essential but must be combined with simulation, feedback, and organizational support